EFL Undergraduate Students’ Politeness Strategy in Online Classroom Interaction - Indra Nabila Zahra; Natalia Anggrarini; Atikah Wati; Indra Yoga Prawiro; Gina Larasaty (International Journal of Science Education and Cultural Studies, 2023)
In an online classroom, the students rely on the textual message to construct and interpret meaning. They should select their sentences carefully to avoid misunderstanding by delivering them politely. This study aims to investigate the type of politeness strategies used by undergraduate students in online interaction in WhatsApp Groups. Using descriptive qualitative, with a case study design, this study used Documentation as the instrument. The data was collected from the screenshots of the interaction in the Class WhatsApp Group. The result showed that the undergraduate students used four types of politeness strategies with positive politeness shown to reflect their good relationship with classmates. The sub-category of politeness was found dominantly in giving gifts. The students used it to compliment and thank their classmates. It is a form of appreciation and acknowledgment to other students. This study was limited by the narrow focus of politeness strategy while it is possible to investigate further the different situations of the classroom and the platform.